Association Between Hair Cortisol, Sarcopenia, and Sarcopenic Obesity: Results From the ELSA ‐Brasil Study - Christiano Barbosa da Silva; Isiyara Taverna Pimenta; Rosane Harter Griep; Arlinda Barbosa Moreno; Isabela Judith Martins Bensenor; Sandhi Maria Barreto; Maria Inês Schmidt; Anissa Daliry; Maria de Jesus Mendes da Fonseca (AGING MEDICINE, 2026)
ABSTRACT Objectives Hair cortisol has been increasingly used as an important biomarker of chronic stress, as it reflects prolonged systemic exposure to cortisol over time. Such exposure has been associated with alterations in body composition; however, the associations with sarcopenia and sarcopenic obesity have still received little attention in the scientific literature on aging. The study aimed to assess the association between hair cortisol, dynapenia, sarcopenia, and sarcopenic obesity in a multicenter and multiethnic Brazilian cohort. Methods The criterion used to classify sarcopenia was specific to the study population, and the categories used were dynapenia (reduced muscle strength), sarcopenia (reduced muscle strength and mass), and sarcopenic obesity (≥ 38% body fat plus sarcopenia). Hair cortisol levels ( pg/mg ) were divided into three categories: Low (< 40), normal (40 to 128), and high (> 128). Simple and multiple logistic regression analyses were used to verify the association between hair cortisol, reduced muscle strength, sarcopenia, and sarcopenic obesity. The final model was adjusted for sex, BMI, hypertension, diabetes, smoking, physical activity, and race/ethnicity, and odds ratios ( OR ) and 95% confidence intervals ( 95% CI ) were calculated. Results A total of 947 participants were included (aged 54 to 82 years, mean age 67.1 years, 63.7% women). Participants with high hair cortisol levels showed lower odds of reduced muscle strength ( OR: 0.796; 95% CI: 0.504–1.255), suggesting an inverse association; this was not statistically significant. However, no significant association was seen between chronic stress and sarcopenia ( OR: 1.106; 95% CI: 0.555–2.206 ) or sarcopenic obesity ( OR: 0.607; 95% CI: 0.162–2.279 ). Conclusions In a sample of Brazilian adults, hair cortisol level, a measurement technique not affected by physiological fluctuations, was not associated with reduced muscle strength, sarcopenia, or sarcopenic obesity.